Posisi Perdagangan Karet Indonesia Dalam Menghadapi Pasar Global - Sang Saniaka Tajulfitri (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
Rubber is one of Indonesia's largest commodities after palm oil, and 85% of its production is carried out by small farmers. This plant has strategic value and is a plant that contributes to foreign exchange for the nation. At present Indonesia's Trade Specialization Index (ISP) is a rubber exporting country, based on the calculation of the average ISP for the 2014-2018 period, with the value of Indonesian ISPs at 0.54. This shows that Indonesian rubber commodities are in the maturation stage in world trade or have very strong competitiveness.